Environments for Multi-Agent Systems. [electronic resource] : Third International Workshop, E4MAS 2006, Hakodate, Japan, May 8, 2006, Selected Revised and Invited Papers - E4MAS 2006 (2006 : Hakodate-shi, Japan); Weyns, Danny.; Parunak, H. Van Dyke; Michel, Fabien; SpringerLink (Online service) (Berlin, Heidelberg : Springer-Verlag Berlin Heidelberg, 2007)
PSZJBL